Evaluation of the combination patch of betel leaf extract (Piper sp.) - ultrasonic assisted extraction as a transdermal delivery system on fibroblast cell formation and collagen density - Valencia, Regina; Trinovita, Elsa; Shinta, Herlina Eka; Toemon, Angeline Novia; Ysrafil, Ysrafil (JURNAL ILMU KEFARMASIAN INDONESIA, 2025)
The combination of red betel (Piper crocatum) and green betel (Piper betle L.) leaves is believed to act synergistically in enhancing wound healing. Transdermal patches offer advantages over conventional topical forms due to their sustained drug release, ease of application, and prolonged therapeutic effect. This study evaluated the histopathological effects of a combination patch containing betel leaf extracts for incision wound treatment in Wistar rats. The studies used an true experimental post-test-only control group design, five groups were tested: a blank patch (K−), a povidone-iodine patch (K+), and combination extract patches at concentrations of 7.5% (K1), 15% (K2), and 30% (K3), applied over 14 days with six animals per group. Patch characteristics were assessed through organoleptic tests, thickness, weight uniformity, folding endurance, and pH, while wound healing was evaluated through histological analysis of fibroblast cell counts and collagen density. Statistical analysis was conducted using the Kruskal-Wallis test followed by Mann-Whitney post-hoc tests. The 30% combination patch (K3) showed the most significant healing effect, with fibroblast counts exceeding 50 cells and dense collagen formation scoring +3. These results indicate that a transdermal patch combining Piper crocatum and Piper betle L. extracts effectively promotes wound healing by enhancing fibroblast proliferation and collagen synthesis.